Lead exposure does not affect baseline and induced innate immunity in quails - Melhado, Gabriel [UNESP]; Pedrobom L., Jorge Henrique [UNESP]; Menegário, Amauri A. [UNESP]; Herrera Montalvo, Luis Gerardo; Cruz-Neto, Ariovaldo P. [UNESP] (Wiley, 2022)
Lead (Pb) is one of the most common metals found in ecosystems in elevated concentrations derived mainly from anthropogenic activities. Pb toxicity is of special concern in birds due to its capacity for bioaccumulation in the liver, bones, and kidneys causing physiological disruptions. Such disruptions can be lethal in a few days after Pb acute intoxication and they are associated with several million deaths of birds. Moreover, Pb may work as an immunosuppressant as it affects the cell-mediated and humoral immune responses, including components of the acute-phase response (APR). We (1) examined the effects of Pb contamination on the innate immune system, body mass, and food intake of Japanese quails (Coturnix coturnix japonica), and (2) evaluated the effects of Pb on its APR after exposing the animals to Pb acetate in drinkable water during 7 days. We found that Pb contamination increased the number of circulating white blood cells (WBCs), but no effect was found on body mass, food intake, the heterophil/lymphocyte (H/L) ratio, and haptoglobin (Hp) concentration. When Pb-exposed birds were injected with lipopolysaccharide from Escherichia coli to activate the APR, they had a negative body mass ratio, reduced food intake, and increased the number of WBCs, the H/L ratio, and the Hp concentration. We conclude that Pb exposure at this dose did not affect baseline values of the constitutive response and that it did not affect the APR of quails, but commend for further studies testing the effect of different Pb doses.
Keywords: acute-phase protein; birds; innate immune system; metal pollution; white blood cells